Aggression and Banter as (de)legitimisation Strategies in Political Debate - Fredrick Friday John; Mathew Kayode Akano; Adegbembo Toluwanimi Oyinlola (Randwick International of Social Science Journal, 2022)
Political debate is an emerging culture in Nigerian politics, aimed at fostering popular democracy, and presenting candidates to electorates to make their choice. But it is likewise a platform for exchanging cynic comments and banters, especially between the contestants, most of the two dominant political parties in Nigeria, the All-Progressive Congress (APC) and the People’s Democratic Party (PDP). This has not been sufficiently researched in studies on political discourse. Extant studies have focused on campaign speeches, acceptance, and concession speeches, among others, using speech acts, socio-stylistics, and critical discourse analysis. This study investigates the comments and rebuttals of Pastor Osagie Ize-Iyamu of the APC, and Governor Godwin Obaseki of the PDP, in the 2020 Edo Governorship Debate. It adopts implicature, explicature and pragmatic acts as theories to, qualitatively, analyse the downloaded and transcribed excerpts from Channels Television’s website, where they were televised to reach millions of people, both in local and international spaces. The results show that both conventional and conversational implicature, and explicature were employed by both aspirants to achieve party and self legitimisation, supremacism, cynicism, and criticism. These are used as campaign strategies. The study concludes that the contestants in the Edo 2020 political debate made it about themselves and their parties. Aggression is initiated and managed as a debate-campaign strategy to canvas for the electorates’ votes.